Dataset for the study of Enhancing the spectral range of plant and bacterial Light-Harvesting pigment-protein complexes with various synthetic chromophores incorporated into lipid vesicles - Hancock, Ashley; Swainsbury, David; Meredith, Sophie; Morigaki, Kenichi; Hunter, Christopher; Adams, Peter (University of Leeds, 2022)
The Light-Harvesting (LH) pigment-protein complexes found in photosynthetic organisms have the role of absorbing solar energy with high efficiency and transferring it to reaction centre complexes. LH complexes contain a suite of pigments that each absorb light at specific wavelengths, however, the natural combinations of pigments within any one protein complex do not cover the full range of solar radiation. Here, we provide an in-depth comparison of the relative effectiveness of five different organic “dye” molecules (Texas Red, ATTO, Cy7, Dil, DiR) for enhancing the absorption range of two different LH membrane protein complexes (the major LHCII from plants and LH2 from purple phototrophic bacteria). Proteoliposomes were self-assembled from defined mixtures of lipids, proteins and dye molecules and their optical properties were quantified by absorption and fluorescence spectroscopy. Both lipid-linked dyes and alternative lipophilic dyes were found to be effective excitation energy donors to LH protein complexes, without the need for direct chemical or generic modification of the proteins. The Förster theory parameters (e.g., spectral overlap) were compared between each donor-acceptor combination and found to be good predictors of an effective dye-protein combination. At the highest dye-to-protein ratios tested (over 20:1), the effective absorption strength integrated over the full spectral range was increased to ~180% of its natural level for both LH complexes. Lipophilic dyes could be inserted into pre-formed membranes although their effectiveness was found to depend upon favourable physicochemical interactions. Finally, we demonstrated that these dyes can also be effective at increasing the spectral range of surface-supported models of photosynthetic membranes, using fluorescence microscopy. The results of this work provide insight into the utility of self-assembled lipid membranes and the great flexibility of LH complexes for interacting with different dyes.
Keywords: FOS: Physical sciences; FOS: Biological sciences